Platycodin D induces apoptosis through JNK1/AP-1/PUMA pathway in non-small cell lung cancer cells: A new mechanism for an old compound - Chen, Shuntai; Wang, Qing; Ming, Sarah; Zheng, Honggang; Hua, Baojin; Yang, Hsin-Sheng (Frontiers in Pharmacology, 2022)
Platycodin D, a triterpenoid monomer, has been shown to possess an anti-tumor effect on various types of cancer. Although Platycodin D has been reported to suppress tumorigenesis, the detailed underlying mechanism remains elusive. Platycodin D treatment significantly reduced the cell viability, decreased the number of colonies, impaired the mitochondrial function, and induced apoptosis in non-small cell lung cancer (NSCLC) cells. To understand the mechanism by which platycodin D induces apoptosis, the expression levels of apoptosis-related proteins were examined, and we found that the expression of PUMA (p53 upregulated modulator of apoptosis) was upregulated upon platycodin D treatment. Knockdown of PUMA resulted in attenuation of platycodin D-induced apoptosis, indicating that PUMA up-regulation is essential for platycodin D to induce apoptosis. The induction of PUMA expression by platycodin D treatment was through activation of AP-1 since mutation of AP-1 binding site in the PUMA promoter abolished the PUMA promoter activity. In addition, the chromatin immunoprecipitation further demonstrated that platycodin D promoted AP-1 binding to PUMA promoter. Moreover, knockdown of JNK1, but not JNK2, significantly abolished the phosphorylation of c-Jun at Ser63 (a component of AP-1), decreased the platycodin D-induced expression of PUMA and cleaved caspase 3, indicating that platycodin D inhibits JNK1/AP-1 signaling pathway. Furthermore, immunohistochemical staining studies showed that tumors from the mice treated with platycodin D activated JNK by translocation of JNK into nuclei, increased phosphorylation of JNK and c-Jun at Ser63 in nuclei, and boosted the PUMA expression. Taken together, our in vitro and in vivo data revealed a novel mechanism by which platycodin D up-regulates PUMA to induce apoptosis through JNK1/AP-1 axis in NSCLC.